2007
DOI: 10.1016/j.expneurol.2007.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic alcohol consumption alters mammalian target of rapamycin (mTOR), reduces ribosomal p70s6 kinase and p4E-BP1 levels in mouse cerebral cortex

Abstract: Reduced insulin sensitivity following chronic alcohol consumption may contribute to alcoholinduced brain damage although the underlying mechanism(s) has not been elucidated. This study was designed to examine the effect of chronic alcohol intake on insulin signaling in mouse cerebral cortex. FVB mice were fed with a 4% alcohol diet for 16 weeks. Insulin receptor substrates (IRS-1, IRS-2) and post-receptor signaling molecules Akt, mammalian target of rapamycin (mTOR), ribosomal p70s6 kinase (p70s6k) and the euk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 22 publications
(23 reference statements)
2
26
0
Order By: Relevance
“…3 Chronic alcohol intake is associated with disruption of the mTOR-signaling pathway in nonlymphoid tissue, such as the mouse cerebral cortex. 7 However, there are limited published data describing the impact of ethanol exposure on this critical signaling pathway in human neoplasia. Importantly, many of the commonly characterized abnormalities present in cancer include loss of phosphatase with tensin homology, and constitutive activation of The average tumor volume of each group (n ϭ 7) with SD is shown as a function of time (*P Յ 2.17 ϫ 10 Ϫ5 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3 Chronic alcohol intake is associated with disruption of the mTOR-signaling pathway in nonlymphoid tissue, such as the mouse cerebral cortex. 7 However, there are limited published data describing the impact of ethanol exposure on this critical signaling pathway in human neoplasia. Importantly, many of the commonly characterized abnormalities present in cancer include loss of phosphatase with tensin homology, and constitutive activation of The average tumor volume of each group (n ϭ 7) with SD is shown as a function of time (*P Յ 2.17 ϫ 10 Ϫ5 ).…”
Section: Discussionmentioning
confidence: 99%
“…50 It has been previously shown that chronic ethanol consumption in mice alters the phosphorylation levels of mTOR, p70 S6 kinase, and 4E-BP1 in mouse cerebral cortex. 7 Chronic ethanol exposure in rats has also been shown to sequester eIF4E from the cap-complex, resulting from an increase in For personal use only. on June 19, 2019.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations